Rancang bangun aplikasi penilaian kinerja guru berbasis web - Yazid Ramadhan; Sharyanto Sharyanto; Samuel Ramos (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
In the world of education, it is not only students who get an assessment but teachers also get an assessment, namely a performance assessment. The performance assessment of a teacher is enforced because now teachers are required to be professional in all fields of education, especially with the existence of teacher constitution regulations and education certification. At Madrasah Ibtidaiyah Nurul Huda the teacher performance appraisal process is still carried out manually with the help of Microsoft Excel which is considered ineffective, takes a long time and is easy for human error to occur. Therefore, a web-based teacher performance appraisal system was created to facilitate the process of assessing teacher performance in Madrasahs. Ibtidaiyah Nurul Huda. This system was created using the Unifield Modeling Language (UML) modeling method and PHP as the programming language and MySQL as the database